Apoplastic Nucleoside Accumulation in Arabidopsis Leads to Reduced Photosynthetic Performance and Increased Susceptibility Against Botrytis cinerea - Daumann, Manuel; Fischer, Marietta; Niopek-Witz, Sandra; Girke, Christopher; Möhlmann, Torsten (Frontiers in Plant Science, 2015)
ABSTRACT Interactions between plant and pathogen often occur in the extracellular space and especially nucleotides like ATP and NAD have been identified as key players in this scenario. Arabidopsis mutants accumulating nucleosides in the extracellular space were generated and studied with respect to susceptibility against Botrytis cinerea infection and general plant fitness determined as photosynthetic performance. The mutants used are deficient in the main nucleoside uptake system ENT3 and the extracellular nucleoside hydrolase NSH3. When grown on soil but not in hydroponic culture, these plants markedly accumulate adenosine and uridine in leaves. This nucleoside accumulation was accpmpanied by reduced photosystem II efficiency and altered expression of photosynthesis related genes. Moreover, a higher susceptibility towards Botrytis cinerea infection and a reduced induction of pathogen related genes PR1 and WRKY33 was observed. All these effects did not occur in hydroponically grown plants substantiating a contribution of extracellular nucleosides to these effects. Whether reduced general plant fitness, altered pathogen response capability or more direct interactions with the pathogen are responsible for these observations is discussed.